Histological and Metabolic State of Dams Suckling Small Litter or MSG-Treated Pups - Claudia Regina Capriglioni Cancian; Nayara Carvalho Leite; Elisangela Gueiber Montes; Stefani Valeria Fisher; Leticia Waselcoski; Emily Caroline Lopes Stal; Renata Zanardini Christoforo; Sabrina Grassiolli (The Scientific World Journal, 2016)
Lactation is an important function that is dependent on changes in the maternal homeostasis and sustained by histological maternal adjustments. We evaluated how offspring manipulations during the lactational phase can modulate maternal morphologic aspects in the mammary gland, adipose tissue, and pancreatic islets of lactating dams. Two different models of litter-manipulation-during-lactation were used: litter sizes, small litters (SL) or normal litters (NL) and subcutaneous injections in the puppies of monosodium glutamate (MSG), or saline (CON). SL Dams and MSG Dams presented an increase in WAT content and higher plasma levels of glucose, triglycerides, and insulin, in relation to NL Dams and CON Dams, respectively. The MG of SL Dams and MSG Dams presented a high adipocyte content and reduced alveoli development and the milk of the SL Dams presented a higher calorie and triglyceride content, compared to that of the NL Dams. SL Dams presented a reduction in islet size and greater lipid droplet accumulation in BAT, in relation to NL Dams. SL Dams and MSG Dams present similar responses to offspring manipulation during lactation, resulting in changes in metabolic parameters. These alterations were associated with higher fat accumulation in BAT and changes in milk composition only in SL Dams.